Two-photon laser printing of 3D multicolor emissive polymer microstructures - Kröger, Finn; Eichelmann, Robert; Sauter, Gabriel; Pollien, Audrey; Tegeder, Petra; Gade, Lutz H.; Blasco, Eva (RSC applied polymers, 2024)
In this study, we aim for the fabrication of precise multi-color 3D microstructures utilizing organic emitters. We have carefully selected dyes with red, green, and blue (RGB) emission characteristics and incorporated them into printable formulations suitable for two-photon laser printing (2PLP). Specifically, we have chosen an OAPPDO derivative, a boron dipyrromethene difluoride (BODIPY), and a coumarin derivative as red, green, and blue emitters, respectively, each functionalized with acrylate groups. The photopolymerizable groups allow for covalent linking to the polymer network formed in the subsequent step, enabling precise control over the incorporation of the desired emitter. The formulations including these three photopolymerizable dyes have been employed to print emissive 3D microstructures via 2PLP. Furthermore, we have studied and optimized their printability, resolution, and emission properties for each case. In a last step, we have fabricated complex multi-material 3D microstructures, demonstrating the versatility and potential application of our method in displays or anti-counterfeiting systems.
Gesehen am 15.07.2024